In vitro comparison of the color degradation of two computer-aided design/computer-aided manufacturing provisional materials: A 12-month simulation - Suzanna Maria Sayegh; Maha Daou; Georges Najjar; Elie Zebouni (The Journal of Indian Prosthodontic Society, 2023)
Aim: This study evaluated the color aging of two computer aided design/computer aided manufacturing (CAD/CAM) provisional materials of different compositions (polymethyl methacrylate and composite resin) after exposure to thermal aging and immersion in coffee for 3, 6, and 12 intraoral months. Setting and Design: The current in vitro study was conducted from September to December 2021 at the Craniofacial laboratory at the Saint Joseph University in Beirut, Lebanon. Materials and Methods: The shades of 2.0 mm thick, 10.0 mm in diameter disk shaped specimens of VITA CAD Temp® and Ceramill® TEMP were measured using the VITA Linearguide 3D MASTER® and a conversion table to extract the CIE LFNx01aFNx01bFNx01 values on a white background (n = 30). Statistical Analysis Used: The color differences ΔE at 3, 6, and 12 months were calculated and analyzed by repeated measures ANOVA followed by Bonferroni multiple comparisons, univariate analyses, and one sample t tests. Results: The mean ΔET1/T0, ΔET2/T0, and ΔET3/T0 values were significantly higher than the cutoff values for acceptability and perceptibility for the VITA CAD Temp® and the Ceramill® TEMP groups. In addition, the increase in ΔE overtime was significantly greater in the Ceramill® TEMP group compared to the VITA CAD Temp® group. Conclusions: The Ceramill® TEMP changed color more and faster than the VITA CAD Temp®. In addition, whether at 3, 6, or 12 months, the color variations of both materials are not only perceptible but also unacceptable compared to the initial shade.